Motives and Consequences of Mergers and Acquisitions - Wang, Juanjuan (2007)
Mergers and acquisitions, nowadays, play significant roles for helping companies achieve certain objectives and financial strategies. This dissertation, firstly, presents three major types of motives of participating in M & A. This part involves the motives that increase or decrease shareholders' value or has uncertain impact on shareholders'value. The motives which increase shareholders' value include the synergy motive, improvement of managerial efficiency, achievement of economies of scale or scope, increased market power and increased revenue growth; whereas the motives which decrease shareholders' value include the agency motive, managerial hubris and free cash flow; the diversification motive has uncertain impact on shareholders' value. Secondly, the effects of engaging in M & A are examined based on four approaches in literature review. Generally speaking, M & A increase shareholders' value for the target company, whereas they decrease shareholders' value for the acquiring company or the newly combined company. Lastly, this dissertation advances quantitative research methodology- an accounting study-to measure the changes in the financial performance of the target and the acquiring company.